How programme design and local context shape the lasting effects of cash and food transfers - Ahmed, Akhter; Hidrobo, Melissa; Hoddinott, John F.; Kolt, Bastien; Roy, Shalini; Tauseef, Salauddin (VoxDev, 2024)
A transfer programme in Bangladesh led to sustained consumption increases and reduced poverty four years post-programme, but design and context mattered. Cash and food transfer programmes in low- and middle-income countries have been shown to be highly effective in increasing household consumption and reducing household poverty in the short term ​(Bastagli et al. 2016, Hidrobo et al. 2018, ​Borga and D’Ambrosio 2021, Ravallion 2016​​). But evidence on whether they sustain longer-term impacts after programmes end is more mixed. Some studies of transfer programmes show significant sustained medium- to long-term impacts on consumption and poverty (​e.g. Carneiro et al. 2021, Stoeffler et al. 2020, ​Macours et al. 2022​)​, but others show effects fading out (e.g. Handa et al. 2019, Cahyadi et al. 2020, Haushofer and Shapiro 2018 ​)​. Some interventions combining transfers with additional components such as cash “plus” programmes or multi-faceted graduation models sustain impacts on consumption four to ten years post-intervention (Bandiera et al. 2017, Banerjee et al. 2022), while others do not (Brune et al. 2022).